The Development of Social Function Questionnaire for Chinese Older Adults - Liu, Conghui; Wang, Yunping; Li, Jing; Xing, Xinzhu; Chen, Xiaojuan; Liu, Jianbing; Wu, Xuanna (Frontiers in Psychology, 2022)
Objectives Social function is an important indicator for physical and psychological health of older adults. However, there is a lack of a standardized questionnaire for measuring social function of older adults. This study developed a questionnaire to assess Chinese older adults’ social function. Methods We used three samples (N = 2,257 aged ≥60 years) to test the reliability and validity of the questionnaire. Results Based on exploratory and confirmatory factor analyses with two samples, the final version of Social Function Questionnaire for Chinese Older Adults (SFQCOA) contained three dimensions with 12 items: social support, social adaptation, and social engagement. Criterion validity test with the third sample showed that SFQCOA was positively related to the healthy indices and negatively related to the unhealthy indices. Conclusion The validity and reliability of the questionnaire reach the requirements of psychometric standards, suggesting it is an effective tool for measuring social function of older adults.